Strategic Adaptability vs Socioemotional Wealth Preservation: A Systematic Review of Family Firm Responses to Digitalization and Globalization - Mugi Harsono; Versiandika Yudha Pratama; Alfiansyah Deviar; Tri Dana Pamungkas; Sulastri (Global Research Collaboration, 2026)
Family firms are distinguished by a fundamental duality between economic performance and the preservation of socioemotional wealth (SEW) comprising family control, identity, legacy, and emotional attachment. As digitalization and global competition intensify, these firms face persistent tensions between strategic adaptability and safeguarding non-economic priorities. However, existing literature addresses this tension in fragmented, single-level silos, separately examining digital transformation, SEW, governance, or internationalization without an integrative synthesis. To build an integrative theoretical understanding, this study adopts a paradox perspective and conducts a systematic literature review following the PRISMA 2020 protocol, searching the Scopus database from 2016 to 2025, where an independent dual-reviewer screening process narrowed 238 initial records to 24 eligible articles for thematic synthesis, with the aim of developing a multi-level framework linking individual leadership and succession dynamics, organizational dynamic capabilities, and macro-environmental pressures. The synthesis reveals three key insights: SEW operates as both a constraint and an enabler, fostering risk aversion yet simultaneously serving as a strategic resource for long-term stakeholder trust and sustainability; successful adaptation depends on dynamic capabilities across individual, family-transfer, and organizational levels, coupled with governance quality and intergenerational succession; and family firms deploy distinct response pathway that transform family values into assets for green innovation and business model renewal. Consequently, this review concludes that sustained success requires integrating adaptability and preservation into a coherent vision, advancing SEW theory through a dynamic-tension perspective and identifying actionable mechanisms like family narratives and board involvement. However, given the predominance of cross-sectional and single-country designs, it urges future longitudinal, cross-country, and multi-level research on emerging frontiers including artificial intelligence adoption, digital governance, and sustainability transitions.